Angka kejadian miopia pada anak usia sekolah dasar di Kecamatan Banjararum Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Reny Setyowati; Indra Tri Mahayana; Tri Winarti; Suhardjo Pawiroranu (Journal of Community Empowerment for Health, 2019)
Refractive disorders begin to affect many children and become a burden of disease in the community due to lack of awareness by parents and screening by health workers. This research was a cross-sectional study and carried out at screening of visual acuity in primary school-aged children. A total of 38 children aged 6 - 12 were the subjects in this study. This research was conducted in Banjararum sub-district, Kulon Progo Regency, Yogyakarta Special Province in September 2018. The average age of subjects was 8.8 ± 1.4 years. Result showed refraction status before correction (uncorrected refractive error/URE) with mean visual acuity of 0.3 logMAR (equivalent to 6/12 Snellen). The most common refractive disorders were myopia simplex (63.2%) and 38.8% of subjects experienced moderate visual impairment. After being corrected, as much as 97.4% of subjects reached normal vision. Burden of undiagnosed refractive disorders in rural population was high even though the visual disturbance is reversible.